Speech style used in Jimmy Kimmel Live talk show (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This research aimed to analyze the use of speech style and the factors that influenced the use of speech style in the Jimmy Kimmel Live Talk Show in all episodes that were aired in November 2021. Speech style is the choice of words based on the level of formality used by a person in communicating, which is influenced by several factors. In this research, the researcher applied Joos' (1976) theory of speech style and Holmes' (2013) theory of factors that influenced the choice of speech style. This research was classified as qualitative descriptive. All of the data in this research were taken from the conversation subtitles between the host and the guest/s, which contained various types of speech styles and were transcribed into the text form. Then, the collected data were classified based on the types of speech styles. After that, the factors that influenced the host and the guest/s to use the speech style were analysed. Based on the results of the research, there are four of the five types of speech styles in this research. Frozen speech style was not found in this research. The four speech styles found in this research were formal (6%), consultative (12%), casual (81%), and intimate (1%), the dominant type of speech style is casual speech style and the least one is intimate speech style.